DETERMINANT FACTORS AFFECTING THE VALUE OF MANUFACTURING COMPANIES LISTED ON THE IDX DURING 2018-2020 - Christie, Tiara; Susanto, Liana (Graduate Program of Universitas Tarumanagara, 2023)
The purpose of this study is to obtain empirical evidence regarding the effect of profitability, liquidity, capital structure, institutional ownership, and company growth on the value of manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2020 period. This study used a sample of 34 manufacturing companies selected using the purposive sampling method. The data in this study were analyzed by multiple linear regression analysis techniques using the EViews 12 SV program. The results of this study show that profitability, institutional ownership, and company growth have a significant influence on the value of the company. Meanwhile, liquidity and capital structure do not have a significant influence on the company value.